Health-care service utilization in substance abusers receiving contingency management and standard care treatments - Olmstead, Todd A.; Cohen, Jeffrey P.; Petry, Nancy M. (Addiction (Abingdon, England), 2012)
ABSTRACT Aim  To determine the impact of standard care and contingency management treatments on the utilization of general health‐care services by substance abusers. Participants, design and measurements  This secondary analysis pooled 1028 treatment‐seeking substance abusers from five randomized clinical trials that compared the effects of standard care (SC, n = 362) to standard care plus contingency management (CM, n = 666). In each trial, subjects in the CM condition showed significantly greater reductions in substance use than their SC counterparts. For each subject, utilization of 15 general health‐care services was measured 1 year prior to treatment intake and up to 9 months following treatment intake. Post‐intake utilization data were prorated to be comparable to the 1‐year pre‐intake data. Paired t‐tests evaluated changes in service utilization pre‐ and post‐intake, and difference‐in‐differences regression models were used to estimate the impact of CM, compared to SC, on changes in the utilization of each of the 15 health services. Setting  Out‐patient community substance abuse clinics in Connecticut and Massachusetts, USA. Findings  Utilization of several types of out‐patient services increased significantly between the pre‐ and post‐intake periods [e.g. dental visits (0.47, P < 0.001), community health center visits (0.50, P < 0.001), visits to a mental health professional office (1.03, P = 0.001)], while in‐patient hospital care for mental health problems decreased significantly (−3.50 nights, P < 0.001). A substantial portion of these changes occurred during the treatment period. No significant differences were found between the two treatment conditions. Conclusions  Initiating out‐patient substance abuse treatment is associated with changes in general health‐care service utilization, independent of the type of treatment offered.